Effect of Blurring Boundaries between Work and Non-Work on Work Performance and Life Quality of University Teachers - MALIK, DR.MISBAH; AZHAR, DR.SARA; RAFIQ, NOREEN (The journal of contemporary issues in business and government, 2021)
Boundaries between work and non-work become increasingly blurred by teachers in educational institutions especially at university level. It is important to understand and observe boundaries of work and non-work to improve their work performance and life quality. This study attempted to provide an insight by measuring the effect of blurring the boundaries between work and non-work on work performance and life quality of university teachers. Correlation research design based on a survey method was used to conduct this study. Teachers of all the departments of University of the Punjab, Lahore were the population of the study. A sample of 100 teachers was selected through multi-stage sampling technique. Self-developed and validated questionnaire was used to measure the variables of the study. A pilot study was conducted to validate the instrument. Descriptive and inferential statistics (t-test, Pearson Correlation & Regression analysis) were applied to analyze the data. As a result of the study, it was determined that the university teachers are blurring the boundaries of work and non-work. A significant difference was found in the perception of teachers about blurring boundaries between work and non-work in terms of gender, marital status and discipline (science & social sciences). However, there was no significant difference in the perception of university teachers regarding their teaching experience and residence. Moreover, a positive relation of blurring boundaries between work and non-work with work performance and life quality of university teachers was determined. It was also concluded that blurring boundaries between work and non-work is a significant predictor of work performance and life quality of university teachers. The results of the study suggested that practitioners and policy makers should adjust the policies and culture of educational institutions to help teachers manage their work-life boundaries.